A systematic review of skin closure techniques in primary cleft lip surgery. (29th May 2014) - Pepper, H.B.; Perry, R.; Ness, A.; Sandy, J.; Thomas, S.
Abstract Aim To carry out a systematic review of the published evidence for skin closure techniques in primary cleft lip surgery. Methods Five electronic databases were searched from their inception to February 2013 to identify all relevant studies of wound closure techniques in primary cleft lip surgery. Two reviewers independently determined eligibility of studies, assessed the methodological quality of the included studies and extracted data. Results Six eligible studies were included. Five were observational studies so were prone to bias. One was a randomised controlled study. Four compared adhesive with sutures, one compared adhesives with steri‐strips and one compared absorbable and non‐absorbable sutures. No cases of dehiscence (primary outcome measure) were reported. The methodological quality of all the included studies was poor. Conclusions There is currently insufficient evidence to guide clinical practice for incision closure in primary cleft lip surgery. Adequately powered randomised controlled trials are required to address this issue.